Molecular Pharmacology - Catala, Angel; Ahmad, Usama (IntechOpen, 2020)
This book concentrates on recent developments related to the application of original structural biology, biochemistry, biophysics, physiology, genetics, and molecular biology as well as basic pharmacological problems that offer mechanistic insights that are generally significant for the field of pharmacology. Written by experts, chapters cover such topics as drug transport mechanisms and drug-receptor complexes. This volume offers up-to-date, expert reviews of the fast-moving field of molecular pharmacology.